Pengaruh Pelatihan Profesional, Pertimbangan Pasar Kerja, Personalitas Dan Lingkungan Kerja Terhadap Minat Mahasiswa Akuntansi Berkarir Menjadi Akuntan Publik - Rosmalinda, Lica; Zanaria, Yulita; Nusantoro, Jawoto (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
The study aims to analyze the Effect of Profesional Training 1; Job Maket Considerations 2; Personality 3; and Work Environment 4; Against the Interest of Accounting Students 5; Career Becoming a Public Accountant. The type of research used in this study is quantitative with a descriptive approach, in this study using as many as 484 respondents. The sampling technique in this research uses Nonprobability Sampling by using Puposive Sampling by using several respondent criteria so as to obtain a sample of 95 respondents. The results of this study indicate that the Professional Training in Considerations of the Job Market, Personality and Work Environment partially or simultaneously influences the Interest of Accounting Student in a Career to Become a Public Accountant.